Ճարապլուսի հայ համայնքի պատմութիւնը - Ֆիշենկճեան, Անի (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Армянская община Джараблуоса в Сирии представила мозаику армянских иммигрантов, переживших Геноцид. Большинство из них мигрировало, особенно из Пережика, Урфы, Айнтапа, Эйнеша, исторического Нисипина и Джибина. Благодаря совместной работе трех деноминаций общины (Апостольской, Католической и Евангелической) Джараблуос стал армянской общиной, которая за свою почти пятидесятилетнюю историю внесла свой вклад в экономическое и культурное развитие как самой общины, так и всего города. Своими церквями и образовательными учреждениями община способствовала делу сохранения армянской идентичности и боролась против широко распространенного турецкого языка. The Armenian community of Jarablous in Syria presented a mosaic of Armenian immigrants who survived the genocide. Most of them migrated, especially from Perejik, Urfa, Ayntap, Einesh, historical Nisipin and Jibin. Thanks to the collaboration of three denominations of the community — Apostolic, Catholic and Evangelical, Jarablous became the Armenian community, where during its nearly fifty-year history, it contributed to the economic and cultural development of both the community and the entire city of Jarablous. The community, with its churches and schools, supported the preservation of the Armenian identity and fought against the widespread use of the Turkish language.
Keywords: Պատմաբանասիրութիւն